2015
DOI: 10.1111/jdv.13325
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting susceptibility from exogenous triggers: the model of alopecia areata and associated inflammatory skin diseases

Abstract: AA patients have a higher incidence of various T-cell-driven inflammatory skin diseases than the normal population, a phenomenon which might relate to over-activation of skin-homing T cells and to specific immune triggers as the primary cause of inflammation. More importantly, we showed that by using AA as a model disease, our approach of intra-individual comparison of distinct inflammatory responses in the same patient is feasible and offers the unique possibility to gain insights into disease pathogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(68 reference statements)
0
16
1
Order By: Relevance
“…A genetic predisposition to multiple autoimmune disease development could also be suspected in our patient, considering his positive family history. The association of either AA or EBA with other autoimmune disorders has been described, although we did not find reports of patients with both AA and EBA. In this context, the occurrence of EBA during SADBE treatment may represent a simple coincidence in a patient already having another autoimmune disease.…”
Section: Discussioncontrasting
confidence: 84%
“…A genetic predisposition to multiple autoimmune disease development could also be suspected in our patient, considering his positive family history. The association of either AA or EBA with other autoimmune disorders has been described, although we did not find reports of patients with both AA and EBA. In this context, the occurrence of EBA during SADBE treatment may represent a simple coincidence in a patient already having another autoimmune disease.…”
Section: Discussioncontrasting
confidence: 84%
“…A retrospective study in Taiwan found that patients with alopecia areata had higher hazard ratios for autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus and psoriasis within the 3-year follow-up period than healthy controls 44 . In addition, increased prevalence of other forms of inflammatory skin disease such as atopic dermatitis, vitiligo, psoriasis and lichen planus were found than in controls, suggesting that patients with alopecia areata are at increased risk of developing variety of T-cell driven inflammatory skin diseases 45 . Severe alopecia areata might be accompanied by nail changes 20 .…”
Section: Concurrent Diseasesmentioning
confidence: 99%
“…Therefore, this older assay variant may be recruited to dissect the relative functional contribution of patient genetics to the pathobiology of AA initiation [5,112,113,114] (Supplementary text 5). …”
Section: Murine Models Of Aamentioning
confidence: 99%